Plan de mejoramiento a la empresa productora y comercializadora Decasa muebles y decoración de la ciudad de Armenia (2015)
“Decasa Muebles & Decoracion” is a Company dedicated to produce and sell home furnishing and decorations. Lately customers have been unsatisfied about the product deliver. But, thanks to an analysis, it has been founded another factors that avoid company to works well. In this way it has been established some objectives to help company to improve its performance both internally and externally. These objectives are directed towards implementing an improvement plan to generate competitive advantages and proper operation of the company. The analysis is descriptive so the results of last investigations are showed with no changes. The research method is deductive whereby it is taken a general fact and, through analysis, it is derived particular facts. Secondary research sources will be handled through databases and research to find an improvement plan. Primary research sources will be Surveys and interviews. As conclusions it is described how, from an original problem, arise another important problems. It is too mentioned the valuable contribution of the theoretical bases to the development of a business improvement plan.